Analysis of stored carbon reserves in trees in the green open spaces of Panatayuda Park, Bandung City, and surrounding areas - Putra, Kurnia Sandi Nugroho Dwi; Hizqiyah, Ida Yayu Nurul; Gurnita, Gurnita (Jurnal Mangifera Edu, 2024)
Climate change and global warming are partly caused by increasing air pollution. This air pollution results in incomplete carbon combustion, producing toxic gases. Carbon is a key component used by plants in the photosynthesis process. Therefore, trees play an important role in reducing pollution and lowering environmental temperatures that trigger climate change and global warming. The purpose of research on carbon reserves is to provide data for the future management of urban parks, utilizing them for climate change mitigation. The method used in this research is descriptive quantitative. Sampling in this study used the census method with purposive sampling, where all trees with a diameter of ≥ 20 cm were taken as samples. The highest biomass and carbon reserve values stored in trees in Panatayuda Park were found in Ficus elastica, with a biomass value of 51,752.77 kg and a carbon reserve value of 25,876.39 kg. Meanwhile, the lowest values were found in Pterocarpus indicus, with a biomass value of 807.39 kg and a carbon reserve value of 403.69 kg. The total carbon reserve in trees in Panatayuda Park is 79,122.21 kg, with a total biomass of 140,244.41 kg.